Reference service user’ satisfaction at the Animal Husbandry Faculty Library, Universitas Padjadjaran - Nono Hermansyah; Novi Mayasari; Nining Winingsih; Agus Darmawan; Muhammad Rifqi Ismiraj (Jurnal Kajian Informasi dan Perpustakaan, 2022)
Reference services satisfaction assessment in libraries are one of the factors that determine the satisfaction of library users. Therefore, periodic improvement and development of reference services is required. This study was aimed to determine the extent of user satisfaction with reference services that have been implemented in the Library of the Faculty of Animal Husbandry, Universitas Padjadjaran. This study employed a quantitative descriptive approach based on survey to 132 respondents representing each academic year. The survey data were analyzed descriptively and presented in graphs. The questions in the survey cover four topics, namely the ease of borrowing and returning procedures, staff performance, reference information access, and library facilities. The results showed that respondents answered satisfied with a consistent level across the topics measured above. Even so, improvements are needed, especially in the aspect of library facilities, which are marked by responses with low scores. Service improvement in these four aspects can generally be focused on changing the paradigm from "library-centered" to "user-centered" by accommodating the expectations and desires of most users. In addition, after conducting training on access to reference collections, respondents answered that the training was considered very useful and was expected to be carried out periodically. In conclusion, users are satisfied with the reference service at the Faculty of Animal Husbandry Library, Universitas Padjadjaran. In addition, the training program on access to library collections has been successfully implemented and felt very useful by respondents and can be categorized as a service improvement activity.